2009
DOI: 10.1002/jso.21465
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a scoring system to predict non‐sentinel lymph node metastasis in melanoma

Abstract: Using cutoff values of 2 and 5 mm for total SLN metastasis, prediction of NSLN metastasis can be made in melanoma patients. Patients with less than 2 mm of total SLN metastasis are unlikely (<3.67% likelihood) to harbor NSLN metastasis; these patients may not benefit from additional nodal dissection beyond SLNB.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 21 publications
0
6
0
1
Order By: Relevance
“…Nowadays, several studies have been committed to finding the signature of melanoma metastasis. Cadili et al (2010) considered the 2 and 5 mm for total sentinel lymph node metastasis as the cutoff value, which could effectively predict the non-sentinel lymph node metastasis in melanoma patients. Wardwell-Ozgo et al (2014) demonstrated that homeobox transcription factor A1 (HOXA1) mediated the cell invasion in melanoma cells, and primary tumors with high-expression HOXA1 were high-risk metastasis subgroups.…”
Section: Discussionmentioning
confidence: 99%
“…Nowadays, several studies have been committed to finding the signature of melanoma metastasis. Cadili et al (2010) considered the 2 and 5 mm for total sentinel lymph node metastasis as the cutoff value, which could effectively predict the non-sentinel lymph node metastasis in melanoma patients. Wardwell-Ozgo et al (2014) demonstrated that homeobox transcription factor A1 (HOXA1) mediated the cell invasion in melanoma cells, and primary tumors with high-expression HOXA1 were high-risk metastasis subgroups.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, if absence of metastasis to the non‐SLN can be precisely predicted at the time of the SLNB, it would be possible to avoid the aforementioned complications without impairing the surgical curability. Multiple parameters used for microscopic classifications of metastatic SLN have been reported to date as being useful for the prediction of additional lymph node positivity, including the metastatic area, 10–12 number of positive SLN 13,14 and a combination of multiple factors; 15–19 of these, the following factors were re‐evaluated in this study: maximum diameter (maximum diameter of the largest tumor lesion in the SLN), 4,20–24 invasion depth (depth of tumor invasion measured from the capsule of the SLN) 6,25–27 and microanatomic location (microanatomic location of the tumor deposit within the SLN) 7 . The factors that were identified as being predictive of an additional lymph node positivity rate of 0% were a maximum diameter of the lesion of less than 0.1 mm 20 or not more than 0.2 mm, 22 an invasion depth of not more than 1.0 mm, 25 a subcapsular microanatomic location, 7 a metastatic area of not more than 0.3 mm 2 , 11 presence of less than two positive SLN, 14 and a combination of factors, comprising an invasion depth of not more than 2 mm, a metastatic area of not more than 10 mm 2 and absence of perinodal involvement 15 .…”
Section: Discussionmentioning
confidence: 99%
“…It may be possible to suggest omission of CLND or reduction in the extent of regional lymphadenectomy in such patients. There have also been reports recently documenting prediction of additional lymph node positivity based on scoring systems devised using the patient background characteristics and characteristics of the primary lesion, besides the above‐mentioned microscopic classification of metastatic SLN 18,19,28,29 . Of these scoring systems, the N‐SNORE 29 appears to be of particular interest, as it seems to offer the promise of more appropriate prediction of additional lymph node positivity than any of the currently published classification systems.…”
Section: Discussionmentioning
confidence: 99%
“…Azoknál a betegeknél, akiknél pozitív SLN került eltávolításra, a publikált közlemények eredményei szerint az elvégzett blokkdisszekcióval hozzávetőlegesen 20%-ban észleltek további pozitív nyirokcsomót. Azok a faktorok, amelyek a leginkább előrejelzik a további nyirokcsomó pozitivitást, a következők: a SLN legnagyobb mérete, az érintett sentinel nyirokcsomók száma, a metasztázis elhelyezkedése/megjelenése a nyirokcsomón belül (subscapuláris, vagy parenchymalis), és a primer tumor jellemzői, mint vastagság, ulceráció (32,56,(63)(64)(65)(66)(67)(68)(69)(70)(71)(72)(73)(74)(75).…”
Section: A Blokkdisszekció Prognosztikai Jelentősége éS Terápiás Hasznaunclassified